Efficiency estimate of feedback application in data transmission system - Корчинский, Владимир Викторович; Большаков, Сергей Иванович (Eastern-European Journal of Enterprise Technologies, 2012)
The presence or absence of feedback presupposes the use of a certain algorithm of error protection. In data transmission systems without feedback the error correction in code combinations is performed during the decoding for the account of the checksum of noise combating code or multiple repetition of the same message. In the feedback transmission systems, the noise combating code is used in the mode of errors detection in the code combinations with their correction through retransmission. Unfortunately, the existing literature on transmission systems does not provide corresponding theoretical material, which justifies the utility of the feedback taking into consideration the conditions of data transmission through the communication channel, so research in this area is important. The article considers the condition, under which the use of feedback in the transmission system increases its effective transfer rate. In order to justify the use of feedback in the data transmission system with the set parameters of discrete channel, the method of comparative evaluation by means of equivalent error probabilities was suggested. This method of evaluation can be used to control the modes of the adaptive data transmission system